Associated bacteria of different life stages of Meloidogyne incognita using pyrosequencing‐based analysis. (25th March 2015) - Cao, Yi; Tian, Baoyu; Ji, Xinglai; Shang, Shenghua; Lu, Chaojun; Zhang, Keqin
<x xml:space="preserve">Abstract</x> The root knot nematode (RKN), Meloidogyne incognita, belongs to the most damaging plant pathogens worldwide, and is able to infect almost all cultivated plants, like tomato. Recent research supports the hypothesis that bacteria often associated with plant‐parasitic nematodes, function as nematode parasites, symbionts, or commensal organisms etc. In this study, we explored the bacterial consortia associated with M. incognita at different developmental stages, including egg mass, adult female and second‐stage juvenile using the pyrosequencing approach. The results showed that Proteobacteria, with a proportion of 71–84%, is the most abundant phylum associated with M. incognita in infected tomato roots, followed by Actinobacteria, Bacteroidetes, Firmicutes etc. Egg mass, female and second‐stage juvenile of M. incognita harbored a core microbiome with minor difference in communities and diversities. Several bacteria genera identified in M. incognita are recognized cellulosic microorganisms, pathogenic bacteria, nitrogen‐fixing bacteria and antagonists to M. incognita. Some genera previously identified in other plant‐parasitic nematodes were also found in tomato RKNs. The potential biological control microorganisms, including the known bacterial pathogens and nematode antagonists, such as Actinomycetes and Pseudomonas, showed the largest diversity and proportion in egg mass, and dramatically decreased in second‐stage juvenile and female of M. incognita. This is the first comprehensive report of bacterial flora associated with the RKN identified by pyrosequencing‐based analysis. The results provide valuable information for understanding nematode–microbiota interactions and may be helpful in the development of novel nematode‐control strategies.